Proyeksi Astral: Analisis Wacana Fiksi Posmodern dalam Naskah Film Insidious - Ramis Rauf (POETIKA, 2017)
This study aims to analyze astral projection as a concept of Death and Dying by using a postmodern fiction discourse analysis perspective in Insidious movie script. This study found that astral projection is a capability possessed by a person to leave physical body and explore an astral world or the spirit world. Astral projection is a death and dying concept that is presented as one of the postmodern fictional strategies known as superimposition. This strategy illustrates that there are two worlds that accumulate and co-exist with each other. Its presence is a way of deconstructing thoughts about something that is considered uncanny and unusual as well as a counterpart of totality that puts the ontological side of the existence of something. It is said by McHale (1987) that it is a sister-genre of postmodern fiction. Science fiction explores ontological issues in order to build a good story while postmodern fiction simply presents the problem without having to build a story. Furthermore, both genres can adopt each other's strategies. Meanwhile, postmodern fictional relations and fantasy fiction are the same, borrowing strategies for exploring ontological issues.